TO EVALUATE THE SAFETY AND EFFICACY OF INJECTION FERRIC CARBOXYMALTOSE IN MANAGEMENT OF MODERATE AND SEVERE ANEMIA IN SECOND AND THIRD TRIMESTER PREGNANCY (Journal of Pharmaceutical Negative Results, 2023)
Background: Ferric carboxymaltose (FCM) is a novel and effective drug in raising haemoglobin levels and in particular replenishing iron stores, however there is a limited knowledge about its safety and efficacy in Indian pregnant women. We performed this study to evaluate the safety and efficacy of injection FCM in management of moderate and severe anemia in 2nd and 3rd trimester pregnancy.Methods: Prospective study conducted at Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pune. 30 pregnant patients of moderate anaemia and 30 pregnant patients of severe anaemia with gestational age 20 weeks and above as determined by correlating last menstrual period (LMP) and clinical examination were included. Data was recorded before injection FCM transfusion, followed by two weeks and four weeks post transfusion. Adverse effects post infusion were carefully noted. Data was analysed by GraphPad Prism 8.0.2 software using the repeated measures ANOVA followed by post hoc turkey test wherever required. Statistically significant P-value = 0.05Results: Data was recorded from 60 patients for safety and efficacy out of which 30 patents had severe and 30 had moderate anemia. Haemoglobin level increased significantly after two weeks (0.92g/dL p = <0.0001) and after four weeks (1.92g/dL p = <0.0001) post FCM injection as compared to Hb level before injection. Significant increase in Hb levels was also observed in severe and moderate anemia patients. Increase in Hb levels for severe anemia pateints after 2 weeks (0.96g/dL, p = <0.0001) and 4 weeks (1.96g/dL, p= <0.0001) post FCM injection and for moderate anemia patients 2 weeks (0.89g/dL, p= <0.0001) and 4 weeks (1.88g/dL, p= <0.0001) post FCM injection was observed as compared to Hb level before injection. Patients who received FCM injection in second trimester and third trimester showed significant increase in Hb levels. Second and third trimester patients showed increase in Hb level after 2 weeks (0.93g/dL, p = <0.0001 and 0.89g/dL, p = <0.0001 respectively) and after 4 weeks (1.98g/dL, p = <0.0001 and 1.81g/dL, p = <0.0001 respectively). Post transfusion reaction was observed in 16% of the patients with itching and rashes being the most common.Conclusion: FCM can significantly increase Hb in a shorter amount of time in patients who have ante-partum iron deficiency anaemia, particularly in people who have severe anaemia. Because it is able to deliver a substantial iron dose in a relatively short period of time, FCM may be an effective treatment option for patients who need to replenish their iron stores in a more expedient manner.